No association of alcohol use and the risk of ulcerative colitis or Crohn’s disease: data from a European Prospective cohort study (EPIC) - Bergmann, M. M.; Hernandez, V.; Bernigau, W.; Boeing, H.; Chan, S. S M; Luben, R.; Khaw, K. T.; van Schaik, F.; Oldenburg, B.; Bueno-de-Mesquita, B.; Overvad, K.; Palli, D.; et al. (Springer Nature, 2017)
Background/Objectives:The role of long-term alcohol consumption for the risk of developing ulcerative colitis (UC) and Crohn's disease (CD) is unclear. For the first time, to prospectively assess the role of pre-disease alcohol consumption on the risk of developing UC or CD.Subjects/Methods:Nested within the European Prospective Investigation into Cancer and Nutrition (EPIC-IBD), incident UC and CD cases and matched controls where included. At recruitment, participants completed validated food frequency and lifestyle questionnaires. Alcohol consumption was classified as either: non-use, former, light (≤0.5 and 1 drink per week), below the recommended limits (BRL) (≤1 and 2 drinks per day), moderate (≤2.5 and 5 drinks per day), or heavy use (>2.5 and >5 drinks per day) for women and men, respectively; and was expressed as consumption at enrolment and during lifetime. Conditional logistic regression was applied adjusting for smoking and education, taking light users as the reference.Results:Out of 262 451 participants in six countries, 198 UC incident cases/792 controls and 84 CD cases/336 controls were included. At enrolment, 8%/27%/32%/23%/11% UC cases and 7%/29%/40%/19%/5% CD cases were: non-users, light, BRL, moderate and heavy users, respectively. The corresponding figures for lifetime non-use, former, light, BRL, moderate and heavy use were: 3%/5%/23%/44%/19%/6% and 5%/2%/25%/44%/23%/1% for UC and CD cases, respectively. There were no associations between any categories of alcohol consumption and risk of UC or CD in the unadjusted and adjusted odds ratios.Conclusion:There was no evidence of associations between alcohol use and the odds of developing either UC or CD.
Keywords: Taverne; Medicine (miscellaneous); Nutrition and Dietetics; Journal Article